Bond‐Forming Reactions of Small Triply Charged Cations with Neutral Molecules. Issue 33 (10th July 2013) - Fletcher, James D.; Parkes, Michael A.; Price, Stephen D.
Abstract Time‐of‐flight mass spectrometry reveals that atomic and small molecular triply charged cations exhibit extensive bond‐forming chemistry, following gas‐phase collisions with neutral molecules. These experiments show that at collision energies of a few eV, I3+ reacts with a variety of small molecules to generate molecular monocations and molecular dications containing iodine. Xe3+ and CS23+ react in a similar manner to I3+, undergoing bond‐forming reactions with neutrals. A simple model, involving relative product energetics and electrostatic interaction potentials, is used to account for the observed reactivity.